2002
DOI: 10.1074/jbc.m203399200
|View full text |Cite
|
Sign up to set email alerts
|

Rpf2p, an Evolutionarily Conserved Protein, Interacts with Ribosomal Protein L11 and Is Essential for the Processing of 27 SB Pre-rRNA to 25 S rRNA and the 60 S Ribosomal Subunit Assembly inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae Rrs1p is a nuclear protein that is essential for the maturation of 25 S rRNA and the 60 S ribosomal subunit assembly. In two-hybrid screening, using RRS1 as bait, we have cloned YKR081c/RPF2. Rpf2p is essential for growth and is mainly localized in the nucleolus. The amino acid sequence of Rpf2p is highly conserved in eukaryotes from yeast to human. Similar to Rrs1p, Rpf2p shows physical interaction with ribosomal protein L11 and appears to associate with preribosomal subunits fairly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…A subcomplex in preribosomes that contains ribosome assembly factors Rpf2 and Rrs1,ribosomal proteins rpL5 and rpL11,and 5S rRNA Previous yeast two-hybrid experiments revealed pairwise interactions between Rpf2, Rrs1, and rpL11 Morita et al 2002). In mature yeast ribosomes, rpL11 is adjacent to 5S rRNA and rpL5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A subcomplex in preribosomes that contains ribosome assembly factors Rpf2 and Rrs1,ribosomal proteins rpL5 and rpL11,and 5S rRNA Previous yeast two-hybrid experiments revealed pairwise interactions between Rpf2, Rrs1, and rpL11 Morita et al 2002). In mature yeast ribosomes, rpL11 is adjacent to 5S rRNA and rpL5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions among components of a subcomplex, such as the Nop7-or PeBoW-subcomplex (Lapik et al, 2004;Miles et al, 2005), the Rpf2-subcomplex (Morita et al, 2002;Miyoshi et al, 2004;Nariai et al, 2005;Zhang et al, 2007), or the Arx1-subcomplex (Lebreton et al, 2006), have been inferred from indirect yeast two-hybrid experiments in vivo, GST pulldown assays in vitro, or by assays for genetic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…4) We found that Rrs1 is essential for growth, is localized in the nucleus with enrichment into the nucleolus, and is required for the maturation of 25S rRNA and the assembly of 60S ribosomal subunits. 4,5) We also found that Rrs1 interacts with ribosomal protein L11 and L5-5S rRNA complex, 6,7) and that the normal functioning of Rrs1 is required for the export of 60S ribosomal subunits from the nucleolus to the cytoplasm. 8) Rrs1 is highly conserved in eukaryotes, and is 36.8% identical to its human homolog.…”
mentioning
confidence: 93%